2012
DOI: 10.1371/journal.pone.0051019
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically Produced Pools of Canonical and Dicer-Substrate siRNA Molecules Display Comparable Gene Silencing and Antiviral Activities against Herpes Simplex Virus

Abstract: RNA interference (RNAi)-based sequence-specific gene silencing is applied to identify gene function and also possesses great potential for inhibiting virus replication both in animals and plants. Small interfering RNA (siRNA) molecules are the inducers of gene silencing in the RNAi pathway but may also display immunostimulatory activities and promote apoptosis. Canonical siRNAs are 21 nucleotides (nt) in length and are loaded to the RNA Induced Silencing Complex when introduced into the cells, while longer siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(89 citation statements)
references
References 44 publications
4
85
0
Order By: Relevance
“…In other research, other influenza genes like NP were inhibited by siRNA. Barik S [8] reported that clinical applications of siRNA against respiratory viruses including influenza virus, showed significant success and optimism, which was reviewed by them [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other research, other influenza genes like NP were inhibited by siRNA. Barik S [8] reported that clinical applications of siRNA against respiratory viruses including influenza virus, showed significant success and optimism, which was reviewed by them [9].…”
Section: Discussionmentioning
confidence: 99%
“…SiRNA is performing as a component of RNAi pathway, which is one of the most important regulation's pathways for gene expression in animal cells [7][8][9]. One of the antiviral defenses in vertebrates which include variety of mechanisms to inhibit virus replication is RNA silencing pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Another option to reduce nonspecific effects of dsiRNA is to use enzymatically produced pools of Dicer substrate RNA [20]. Dicer from the protozoan parasite Giardia intestinalis was used to obtain enzymatically produced dsiRNAs.…”
Section: Dicer Substrate Interfering Rnasmentioning
confidence: 99%
“…This review focuses on current strategies of development of siRNA structural modifications for promoting better gene silencing with low risk of side effects, with particular focus on longer siRNA duplexes 25-30 nt in length that mimic Dicer substrates (Dicer substrate siRNA (dsiRNA)) [15][16][17][18][19][20]. Special attention has been paid to the long double-stranded RNA duplexes, which induced effective gene silencing and did not require Dicer-mediated processing of the substrate into smaller units: trimer RNA (tsiRNA) with 63 nt in length and tripartite-interfering RNA (tiRNA) with 38 nt in length [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…One of antiviral defense in vertebrates which includes variety of mechanisms to inhibit virus replication is RNA silencing pathways. Gene silencing, induced by RNAi, is mediated by microRNAs (mirRNA) and small interfering RNA (siRNA) forming Watson-Crick base pairing to a target mRNA, subsequently leading to its sequence-specific cleavage [10,11]. The first term of RNAi was used in the worm Caenorhabditiselegans to explain that dsRNA complementary to a particular gene was more effective in silencing than either strand individually [12].…”
Section: Introductionmentioning
confidence: 99%